Polymercaptan-based polyurethane foams. (November 2016) - Javni, I; Bilić, O; Ljubić, D; Wan, X; Petrović, ZS; Upshaw, TA
Rigid thiourethane foams were prepared from vegetable oil-based polythiols (polymercaptans) and compared with soy- and castor oil-based polyurethane reference foams. Three types of polymercaptans were tested, soybean oil-based one with thiol groups only, epoxidized soybean oil-based with vicinal thiol and hydroxyl groups and castor oil-based with hydroxyl and thiol groups separated with several methylene units. Physical, mechanical, and thermal characteristics of polyol- and thiol based foams were similar to petrochemical foams used as heat insulation materials in construction, appliances, etc.